The pagan lord : a novel - Cornwell, Bernard (New York : Harper, 2014)
"New York Times bestselling author Bernard Cornwell returns to his epic Saxon Tales saga with The Pagan Lord, a dramatic story of divided loyalties, bloody battles, and the struggle to unite Britain.At the onset of the tenth century, England is in turmoil. Alfred the Great is dead and Edward his son reigns as king. Wessex survives but peace cannot hold: the Danes in the north, led by Viking Cnut Longsword, stand ready to invade and will never rest until the emerald crown is theirs. Uhtred, once Alfred's great warrior but now out of favor with the new king, must lead a band of outcasts north to recapture his old family home, that great Northumbrian fortress, Bebbanburg.In The Pagan Lord, loyalties will be divided and men will fall, as every Saxon kingdom is drawn into the bloodiest battle yet with the Danes; a war which will decide the fate of every king, and the entire English nation"--
"Published in Great Britain in 2013 by HarperCollins Publishers"--Title page verso.
Keywords: Alfred, -- King of England, -- 849-899 -- Fiction; FICTION / Historical; FICTION / War & Military; FICTION / Action & Adventure; Great Britain -- History -- Alfred, 871-899 -- Fiction; Historical fiction